Pelaksanaan Diversi Terhadap Tindak Pidana Yang Dilakukan Oleh Anak Di Pengadilan Negeri Bangkinang Oleh : Rica Regina Novianty (Hukum Pidana) - Rica Regina Novianty; Erdianto '; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
The principle of the protection of children, especially on the principle of non-discrimination that prioritizes the best interests of the child and the right to life, survival and development so that the necessary respect for the child's opinion. Thus there emerged an idea for it, that the perpetrators of criminal offenses committed by children should be avoided as far as possible from the criminal justice process. Based on this thinking, it gives birth to a concept called diversion, which is the Indonesian term called diversion or redirection. Diversion is an action or treatment to divert a case of a formal process to process informal or put out criminal child of the juvenile justice system, or put out the perpetrators of criminal acts of the criminal justice system of children. The author has done to several research Pre Trial in First Level Jurisdiction in the province of Riau, and author in the end chose Bangkinang District Court as a test site, because the number of cases Diversi minimal and access is easy to reach in the research process Issues examined in this study are: First, How Diversion Implementation of the offenses committed by children in the District Court Bangkinang? Second, Is Diversion implementation of the offenses committed by children in the District Court Bangkinang has reflected legal protection of the child?This type of research is the study of law Sociological. Source data used are primary data and secondary data, data collection techniques. obtained from interviews and literature study. In this study the authors used a qualitative analysis, in drawing conclusions using inductive method of thinking.The results of this study are the First, implementation of Diversion of the offenses committed by children in the District Court Bangkinang not running optimally, it can be seen from the number of successful cases in Diversion and also the obstacles found by the judge in the effective implementation of Diversion for children such as the number of judges has a child criminal Justice Specifications only two judges, victims' families are determined to not do Diversi, and insisted on proceeding with the criminal. Secondly, protection of children rights based implementation of Diversion District Court Bangkinang not maximized, it is envisaged, from the number of successful cases in Diversion. Suggestions from authors First, the judge must explore ways for the implementation of the Diversion of children committing criminal offenses can be implemented optimally. And deficiencies that become a reason not maximal implementation Diversion can be solved by the parties concerned. Diversion implementation should be maximized since in the investigation. Second, took the seriousness of various stakeholders such as governments, law enforcement and the community to create the legal protection of the child offender so that the goal can be achieved Diversi.Keywords: Diversi - Children - Court Bangkinang